First Provincial Record of Black-crowned Night heron (Nycticorax nycticorax) in West Sumatra and the Summary of Its Sumatran Records - Muhammad Nazri Janra; Aadrean Aadrean; Henny Herwina (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2020)
The Black-crowned Night heron (Nycticorax nycticorax) is a known visitor in Sumatra with more sighting records in the eastern side of the island. Meanwhile, on the west, it was historically recorded from only two offshore islands, namely Nias and Enggano. During the waterbird survey from early 2018 at Pasir Jambak Beach of Padang City in the coastline of West Sumatra, a Night heron was spotted among the colony of mixed egret species. This study aims to update the knowledge of this species in West Sumatra, as well as its general occurrence in Sumatra. This study was conducted by counting the population of each waterbird species found in the research area, while for documentation purposes, a Nikon Coolpix P900 was used to take pictures. Species identification was guided with related books for the Sumatera area. Data then were analyzed and outlined descriptively in accordance with what accumulated from the field survey and online searching. The result showed that the first sighting of Black-crowned Night-heron in West Sumatra follows the common fly-through route of migrant birds in eastern side of Sumatra. The summary of the compiled records of this species indicates that it is probably a vagrant along the western coastline, while it visits more frequently on the eastern side. This is the first record of its kind in the province of West Sumatra, although, previous records cover almost all provinces in Sumatra.